2010
DOI: 10.5194/bg-7-57-2010
|View full text |Cite
|
Sign up to set email alerts
|

Increased ocean carbon export in the Sargasso Sea linked to climate variability is countered by its enhanced mesopelagic attenuation

Abstract: Abstract. Photosynthetic CO 2 uptake by oceanic phytoplankton and subsequent export of particulate organic carbon (POC) to the ocean interior comprises a globally significant biological carbon pump, controlled in part by the composition of the planktonic community. The strength and efficiency of this pump depends upon the balance of particle production in the euphotic zone and remineralization of those particles in the mesopelagic (defined here as depths between 150 and 300 m), but how these processes respond … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 62 publications
7
158
2
Order By: Relevance
“…Chl a concentrations follow predictable annual patterns during the northwestern Sargasso Sea spring bloom ( Figure 1a) (Steinberg et al, 2001;Lomas et al, 2010). Over the period of this data set, Chl a standing stock, integrated over the photic zone (0-140 m), increased with the onset of mixing and peaks 2 months following the DM events.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Chl a concentrations follow predictable annual patterns during the northwestern Sargasso Sea spring bloom ( Figure 1a) (Steinberg et al, 2001;Lomas et al, 2010). Over the period of this data set, Chl a standing stock, integrated over the photic zone (0-140 m), increased with the onset of mixing and peaks 2 months following the DM events.…”
Section: Resultsmentioning
confidence: 91%
“…Two previous studies, based on the same suite of BATS phytoplankton data from 1990 to 1997 (Steinberg et al, 2001) and additional data extending to 2007 (Lomas et al, 2010) have shown that the bloom can begin as early as January and as late as April. These studies show that the calendar month is irrelevant to the timing of the bloom and that rather the month of DM serves as the best indicator of the bloom onset.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations